“Stay indoors with Purdah, men will make the money”: A qualitative study investigating women’s microfinance participation and mobility practices in Bangladesh - Kanig Fatema Akter Bristi; Tunvir Ahamed Shohel; Taufiq-E-Ahmed Shovo; Maherun Nahar Mumu; Hamalna Nizam (PLoS ONE, 2026)
Purpose of this paper This study aimed to investigate the impact of Purdah , a cultural norm, on the economic independence of women who have received microfinance in Bangladesh. The study also sought to understand whether the Purdah norm has an influence on microfinance loans, such as use, control, and repayment, relevant to female borrowers’ mobility practice. Perception, cultural value, and Purdah’s implications for everyday life were also considered. Design/methodology/approach We selected women’s groups in development programs, such as microfinance, as the case for this study. By using a snowball sampling technique, we identified 25 microfinance recipients for interview– mostly women and their spouses living in the Dumuria and Tala Upazilas in the Khulna division of Bangladesh. The research employed thematic analysis to draw conclusions and explain the findings. Findings The study findings show that traditional norms associated with Purdah hinder women’s economic engagement and that the practice of Purdah among women is institutionalized from a very young age, primarily before marriage. The findings further explain that Purdah norms limit women’s mobility, act as a cultural barrier to IGAs, create economic dependence on men, and enable men to control microfinance loans. Therefore, women are not fully in control of their microfinance loans, and microfinance participation appears to be a less satisfactory form of financial inclusion for participants. Practical implications and value of paper This study suggests that viewing Purdah solely as a religious requirement limits understanding of its cultural roots. Cultural interpretation is needed to shape policies and reduce Purdah’s impact on women’s mobility.